Tuberculosis transverse myelitis in pediatric patient - Robert Sinurat (Indoscholar, 2021)
Tuberculosis myelitis usually impact adult patients and associated with tuberculous meningitis, miliary tuberculosis, or human immunodeficiency virus infection. Pediatric tuberculosis myelitis cases without any associated diseases have never been reported. The author reported a case of a pediatric patient with tuberculosis myelitis without any other organ involvement and the outcome after treatment. Girl 13 years old suffered from paraplegia of her lower extremities. Two months before paraplegia she felt weakness in her left leg and followed by the right side. The legs were spastic and ankle clonus was positive. She lost sensation from epigastrium level to her both of legs and difficult to bowel. Laboratories result was normal but spinal magnetic resonance imaging showed hyperintense lesion of spinal cord thoracic vertebrae 5-8. During the laminectomy procedure, there was no any tumor, abscess, or tuberculoma, but the spinal cord looked brown. A biopsy was performed, and the histopathology results showed the granuloma containing lymphocytes, epithelioid macrophages, and datia langhans cells. The patient was treated with anti-tuberculosis chemotherapy for twelve months. Clinical symptoms improved gradually and the patient was able to walk slowly. Tuberculosis myelitis is an inflammatory spinal cord disease and it can cause paralyzed, sensory and autonomic disturbance. Magnetic resonance imaging can differentiate between spinal tuberculosis and spinal tumors, but it will be difficult if there are no signs of vertebral body and discs inflammation. Tuberculosis myelitis should be considered as a differential diagnosis of spinal cord lesions in children and its response to anti-tuberculosis chemotherapy is excellent.